Central role for GSK3β in the pathogenesis of arrhythmogenic cardiomyopathy - Stephen P. Chelko; Angeliki Asimaki; Peter Andersen; Djahida Bedja; Nuria Amat-Alarcon; Deeptankar DeMazumder; Ravirasmi Jasti; Calum A. MacRae; Remo Leber; Andre G. Kleber; Jeffrey E. Saffitz; Daniel P. Judge (JCI Insight, 2016)
Arrhythmogenic cardiomyopathy (ACM) is characterized by redistribution of junctional proteins, arrhythmias, and progressive myocardial injury. We previously reported that SB216763 (SB2), annotated as a GSK3β inhibitor, reverses disease phenotypes in a zebrafish model of ACM. Here, we show that SB2 prevents myocyte injury and cardiac dysfunction in vivo in two murine models of ACM at baseline and in response to exercise. SB2-treated mice with desmosome mutations showed improvements in ventricular ectopy and myocardial fibrosis/inflammation as compared with vehicle-treated (Veh-treated) mice. GSK3β inhibition improved left ventricle function and survival in sedentary and exercised Dsg2mut/mut mice compared with Veh-treated Dsg2mut/mut mice and normalized intercalated disc (ID) protein distribution in both mutant mice. GSK3β showed diffuse cytoplasmic localization in control myocytes but ID redistribution in ACM mice. Identical GSK3β redistribution is present in ACM patient myocardium but not in normal hearts or other cardiomyopathies. SB2 reduced total GSK3β protein levels but not phosphorylated Ser 9–GSK3β in ACM mice. Constitutively active GSK3β worsens ACM in mutant mice, while GSK3β shRNA silencing in ACM cardiomyocytes prevents abnormal ID protein distribution. These results highlight a central role for GSKβ in the complex phenotype of ACM and provide further evidence that pharmacologic GSKβ inhibition improves cardiomyopathies due to desmosome mutations.